Amine liquid deoiling recovery device and recovery method
By using super-hydrophobic and super-lipophilic porous sponge adsorption material and press plate extrusion and desorption technology in the amine liquid desulfurization system, the foaming problem of MDEA amine liquid when the oil phase is present is solved, and efficient amine liquid oil removal and Recycling reduces resource waste and water treatment costs and ensures stable operation of the system.
Patent Information
- Application Number
- CN202310723688.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-19
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-06-19
AI Technical Summary
In the existing amine liquid desulfurization technology, MDEA is prone to foaming when the oil phase is present, resulting in unstable operation of the absorption tower and regeneration tower, and conventional treatment methods lead to waste of amine liquid and increased water treatment costs.
An amine liquid oil removal and recovery device was designed to absorb the oil phase in the amine liquid using superhydrophobic and super-lipophilic adsorption materials (such as porous sponges), and then extrude and desorption through pressing and desorption to achieve separation and reuse of the oil phase. Avoid foaming and waste of amine liquid.
It improves the efficiency and recovery of amine liquids, reduces resource waste and water treatment costs, ensures the stable operation of the desulfurization system, and provides safety guarantees.
Smart Images

Figure CN119158411A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of amine liquid oil removal, and in particular to an amine liquid oil removal recovery device and a recovery method. Background Art
[0002] Amine liquid desulfurization technology is a relatively mature, efficient and simple technology among the three major desulfurization processes of wet, semi-dry and dry methods, and is widely used in the desulfurization fields of flue gas, coal gas, petroleum, etc. Compared with traditional selective desulfurization solvents, the compound amine liquid formula with N-methyldiethanolamine (MDEA) as the main body has the advantages of high stability, good desulfurization selectivity, low regeneration energy consumption and low price. However, MDEA has the disadvantage of easy foaming in the presence of oil phase, which affects the safe and stable operation of the absorption tower and regeneration tower and even the entire deacidification system.
[0003] There are currently two measures to deal with amine liquid foaming. One is to add defoamers. However, since the defoamer itself is also a surfactant and as the oil phase accumulates in the amine liquid, the risk of amine liquid foaming gradually increases. The gradually accumulated impurities will also cause fluctuations in the desulfurization system operating conditions. Another method is amine liquid purification, that is, regular and fixed-point drainage to discharge most of the oil phase and a small amount of amine liquid, but this method causes waste of amine liquid and impact on downstream sewage treatment equipment.
[0004] In view of the shortcomings of the above-mentioned treatment methods for avoiding amine liquid foaming, it is urgent to develop an amine liquid oil removal and recovery device to avoid amine liquid foaming and recover amine liquid. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art in treating amine liquid foaming, such as oil phase accumulation and amine liquid waste, and to provide an amine liquid oil removal and recovery device. The device is used for amine liquid oil removal, has high oil removal efficiency and high amine liquid recovery rate, and avoids the problems of resource waste and increased water treatment cost caused by conventional treatment methods.
[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides an amine liquid oil removal and recovery device, which comprises:
[0007] A first housing and a first accommodating cavity formed around the housing;
[0008] A partition is sealed and arranged in the first accommodating cavity, wherein the bottom of the partition and the first shell form a buffer cavity; and the top of the partition and the first shell form a storage cavity;
[0009] A second shell is arranged above the partition, and the partition and the second shell form an adsorption filtration chamber;
[0010] The adsorption material arranged in the adsorption filtration cavity is used to adsorb the oil phase in the amine liquid; the adsorption material has super hydrophobic and super oleophilic properties;
[0011] A pressure plate is arranged in the adsorption filter cavity and placed above the adsorption material, and the pressure plate squeezes the adsorption material by lifting and lowering; the partition plate and the pressure plate are provided with openings to provide a flow channel for the fluid, so that the fluid can enter the adsorption filter cavity from the buffer cavity through the partition plate, and then enter the storage cavity through the pressure plate;
[0012] A connecting rod mechanism, connected to the pressing plate and passing through the first shell and the second shell, and used for driving the pressing plate to rise and fall;
[0013] The first shell is provided with an oil-free amine liquid outlet, a dirty oil outlet and an oil-containing amine liquid inlet connected to the first accommodating chamber; the oil-free amine liquid outlet is arranged above the partition, and the dirty oil outlet and the oil-containing amine liquid inlet are arranged below the partition.
[0014] A second aspect of the present invention provides an amine liquid oil removal and recovery method, the method comprising:
[0015] (1) Opening the oil-containing amine liquid inlet and the de-oiled amine liquid outlet, closing the dirty oil outlet, the oil-containing amine liquid enters the buffer chamber from the oil-containing amine liquid inlet; flows into the adsorption and filtration chamber from the opening of the partition plate, and the oil phase in the oil-containing amine liquid is adsorbed by the adsorption material in the adsorption and filtration chamber to obtain the de-oiled amine liquid; the de-oiled amine liquid flows out from the opening of the pressing plate, enters the storage chamber, and is discharged from the de-oiled amine liquid outlet;
[0016] (2) When the adsorption material is saturated with adsorption, the oil-containing amine liquid inlet and the de-oiled amine liquid outlet are closed, the dirty oil outlet is opened, and the connecting rod mechanism is driven down to cause the pressure plate to squeeze the adsorption material and discharge the oil phase in the adsorption material. The oil phase flows into the buffer chamber through the opening of the partition plate and is discharged from the dirty oil outlet;
[0017] (3) After the oil phase is removed, the connecting rod mechanism is driven upward so that the adsorption material regains its adsorption capacity and step (1) is repeated.
[0018] Through the above technical scheme, the amine liquid oil removal and recovery device described in the present invention is used for amine liquid oil removal, and has high oil removal efficiency and high amine liquid recovery rate. In particular, when the adsorbent material includes the oil-absorbing sponge described in the present invention, the adsorbent material has super-hydrophobic and super-oleophilic properties, and has a strong adsorption capacity for the oil phase. The super-oleophilic property of the sponge material realizes the separation of the oil phase and the water phase in the flowing oil-containing amine liquid. The oil phase is adsorbed in the porous structure of the sponge because of its stronger affinity with the sponge material; the oil-absorbing sponge is used for oil-containing amine liquid oil removal, has a high selective adsorption capacity for the oil phase, has a large adsorption capacity for the oil phase and can be recycled, and has basically no attenuation in the case of 30 cycles; the oil phase adsorbed by the oil-absorbing sponge is squeezed and desorbed by the pressure plate in the amine liquid oil removal and recovery device, combined with the high resilience of the sponge, the separation of the sponge material and the oil phase can be achieved, thereby realizing the reuse of the sponge material.
[0019] The sponge itself has excellent flame retardant properties, providing safety protection for the sampling process in the petrochemical industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a structural schematic diagram of an amine liquid oil removal and recovery device provided in a preferred embodiment of the present invention;
[0021] Figure 2 is a scanning electron microscope (SEM) image of the oil-absorbing sponge prepared in Preparation Example 1;
[0022] Figure 3 is a scanning electron microscope (SEM) image of the oil-absorbing sponge prepared in Preparation Example 1 after 30 cycles;
[0023] Figure 4 is a scanning electron microscope (SEM) image of the porous melamine-formaldehyde sponge matrix in Preparation Example 1;
[0024] Figure 5 is a scanning electron microscope (SEM) image of the oil-absorbing sponge prepared in Preparation Example 8;
[0025] Figure 6 This is a scanning electron microscope (SEM) image of the oil-absorbing sponge prepared in Preparation Example 8 after being cycled 30 times.
[0026] Description of Reference Numerals
[0027] 1—Linkage 2—Second housing
[0028] 3—Baffle 4—De-oiled amine liquid outlet
[0029] 5—dirty oil outlet 6—absorption material
[0030] 7—First shell 8—Oil-containing amine liquid inlet
[0031] 9—Press plate DETAILED DESCRIPTION
[0032] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0033] In the present invention, unless otherwise specified, directional words such as "up, down, left, right" generally refer to up, down, left, right as shown in the reference drawings; "inside, outside" refer to inside and outside relative to the outline of each component itself.
[0034] A first aspect of the present invention provides an amine liquid oil removal and recovery device, the device comprising:
[0035] A first housing 7 and a first accommodating cavity formed by the housing;
[0036] The partition 3 is sealed and arranged in the first accommodating cavity, the bottom of the partition 3 and the first shell 7 form a buffer cavity; the top of the partition 3 and the first shell 7 form a storage cavity;
[0037] A second shell 2 is disposed above the partition 3, and the partition 3 and the second shell 2 form an adsorption filtration chamber;
[0038] The adsorption material 6 disposed in the adsorption filtration chamber is used to adsorb the oil phase in the amine liquid; the adsorption material 6 has super hydrophobic and super oleophilic properties;
[0039] A pressing plate 9 is arranged in the adsorption filtration chamber and placed above the adsorption material 6, and the pressing plate 9 squeezes the adsorption material 6 by lifting and lowering; the partition plate 3 and the pressing plate 9 are provided with openings to provide a flow channel for the fluid, so that the fluid can enter the adsorption filtration chamber from the buffer chamber through the partition plate 3, and then enter the storage chamber through the pressing plate 9;
[0040] A connecting rod mechanism 1 is connected to the pressing plate 9 and passes through the first shell 7 and the second shell 2, and is used to drive the pressing plate 9 to move up and down;
[0041] The first shell 7 is provided with an oil-free amine liquid outlet 4, a dirty oil outlet 5 and an oil-containing amine liquid inlet 8 connected to the first accommodating chamber; the oil-free amine liquid outlet 4 is arranged above the partition 3, and the dirty oil outlet 5 and the oil-containing amine liquid inlet 8 are arranged below the partition 3.
[0042] The second housing 2 is coaxially disposed inside the first housing 7 and is located inside the storage cavity.
[0043] In the present invention, the material of the partition 3 can be selected from a wide range, as long as it can withstand the pressure generated during the extrusion process and does not deform. According to a preferred embodiment of the present invention, the material of the partition 3 is selected from one of metal, polymer material or ceramic material; preferably selected from at least one of 304 stainless steel and ABS.
[0044] According to a preferred embodiment of the present invention, the apertures of the partition plate 3 and the pressure plate 9 are 5-20 mm and 10-30 mm respectively.
[0045] According to a preferred embodiment of the present invention, the second shell (2) is welded to the area above the opening of the partition plate 3 to prevent dirty oil from contaminating the de-oiling amine liquid pipeline during the extrusion process.
[0046] In the present invention, the connecting rod mechanism 1 is used to drive the pressure plate 9 to rise and fall. The pressure plate 9 descends to compress and squeeze the adsorption material 6 to discharge the oil phase adsorbed by the adsorption material 6; the pressure plate 9 rises, and the adsorption material 6 recovers by its own elasticity and is used again to absorb the oil phase in the oil-containing amine liquid; according to a preferred embodiment of the present invention, the driving stroke of the connecting rod mechanism 1 is set to 5%-80% of the thickness of the adsorption material 6, preferably 50%-80%.
[0047] According to a preferred embodiment of the present invention, the adsorption material 6 includes an oil-absorbing sponge, which includes a three-dimensional porous polymer matrix and a thermosetting resin coated on the three-dimensional porous polymer matrix; the saturated adsorption capacity of the oil-absorbing sponge for oil products is not less than 30 g / g; the saturated adsorption capacity of the oil-absorbing sponge for oil products is still not less than 30 g / g after 30 adsorption-desorption cycles.
[0048] The oil-absorbing sponge of the present invention has super-hydrophobic and super-oleophilic properties while maintaining the high resilience and high porosity of the original three-dimensional porous polymer matrix. The oil-absorbing sponge has good resilience and strong adsorption capacity for oil products.
[0049] According to a preferred embodiment of the present invention, the mass of the thermosetting resin accounts for 0.5-5%, preferably 2-3%, of the total mass of the sponge.
[0050] According to a preferred embodiment of the present invention, the saturated adsorption capacity of the oil-absorbing sponge for oil is 30-50 g / g.
[0051] The oil-absorbing sponge of the present invention has strong selectivity for oil products in oily wastewater, large adsorption capacity for oil products and can be recycled. The adsorption capacity is basically not attenuated after being recycled for 30 times. According to a preferred embodiment of the present invention, the saturated adsorption capacity of the oil-absorbing sponge for oil products is still 30-50g / g after 30 desorption-adsorption cycles.
[0052] In the present invention, the thermosetting resin can be selected from a wide range, and conventional thermosetting resins in the field can meet the requirements of the present invention. According to a preferred embodiment of the present invention, the thermosetting resin is selected from at least one of phenolic resin, epoxy resin, urea-formaldehyde resin, unsaturated polyester resin and silicone resin; preferably selected from at least one of phenolic resin, epoxy resin and silicone resin.
[0053] In the present invention, the three-dimensional porous polymer matrix only needs to have a through-hole structure inside and a porosity greater than 70%. According to a preferred embodiment of the present invention, the three-dimensional porous polymer matrix is selected from at least one of melamine-formaldehyde sponge, polyurethane sponge and ethylene-vinyl acetate sponge, preferably melamine-formaldehyde sponge.
[0054] In the present invention, the pore size of the oil absorbing sponge can be selected in a wide range. According to a preferred embodiment of the present invention, the pore size of the oil absorbing sponge is 10-500 μm, preferably 100-400 μm.
[0055] In the present invention, the porosity of the oil-absorbing sponge can be selected in a wide range. According to a preferred embodiment of the present invention, the porosity of the oil-absorbing sponge is greater than or equal to 60%, preferably greater than or equal to 90%.
[0056] The oil-absorbing sponge of the present invention has super-hydrophobic and super-oleophilic properties. According to a preferred embodiment of the present invention, the static plane contact angle of the surface of the oil-absorbing sponge to water in air is greater than 135°; preferably greater than 145°.
[0057] The oil-absorbing sponge of the present invention has super-hydrophobic and super-oleophilic properties. According to a preferred embodiment of the present invention, the static contact angle of the surface of the oil-absorbing sponge to white oil is less than 30°; preferably 0-20°; more preferably 0°.
[0058] The oil-absorbing sponge of the present invention also has flame retardant properties; according to a preferred embodiment of the present invention, the UL94 vertical burning test grade of the oil-absorbing sponge is above V-2, preferably above V-1; more preferably V-0.
[0059] The oil-absorbing sponges having the above-mentioned characteristics of the present invention can achieve the purpose of the present invention, and there is no special requirement for the preparation method thereof. With respect to the present invention, according to a preferred embodiment of the present invention, the present invention provides a method for preparing the oil-absorbing sponge of the present invention, the method comprising:
[0060] The solution containing the thermosetting resin prepolymer and the curing agent is dispersed into the three-dimensional porous polymer matrix, and cured under vacuum conditions to obtain the oil-absorbing sponge. The preparation method of the present invention disperses (for example, extrusion absorption dispersion, spray absorption dispersion) the solution containing the thermosetting resin prepolymer and the curing agent into the three-dimensional porous polymer matrix and then heats and cures it in vacuum, which can cure the thermosetting resin on the three-dimensional porous polymer matrix while maintaining the high resilience and high porosity of the original three-dimensional porous polymer matrix.
[0061] In the present invention, there is no particular limitation on the dispersion method of dispersing the solution containing thermosetting resin prepolymer and curing agent into the three-dimensional porous polymer matrix, as long as it can be evenly dispersed. According to a preferred embodiment of the present invention, the dispersion method is extrusion absorption dispersion or spray absorption dispersion, preferably extrusion absorption dispersion.
[0062] In the present invention, extrusion absorption dispersion refers to extruding the three-dimensional porous polymer matrix, placing it in a solution containing a thermosetting resin prepolymer and a curing agent, absorbing and restoring it to its original shape, and then extruding it to a certain proportion to discharge the excess solution and disperse it evenly.
[0063] In the present invention, spray absorption dispersion refers to uniformly dispersing a certain amount of thermosetting resin prepolymer and curing agent solution onto the surface of the three-dimensional porous polymer matrix in a spraying manner, waiting for absorption and then heating and curing.
[0064] In the present invention, the curing pressure may be selected in a wide range. According to a preferred embodiment of the present invention, the pressure is 0 to 10 kPa, preferably 3 to 5 kPa.
[0065] In the present invention, the curing conditions have a wide range of optional ranges. According to a preferred embodiment of the present invention, the curing conditions include: a temperature of 80 to 200°C, preferably 100 to 180°C; the curing time can be reasonably adjusted according to actual needs, preferably, the time is 5 to 120 minutes, more preferably 20 to 100 minutes.
[0066] According to a preferred embodiment of the present invention, the method for preparing the oil-absorbing sponge comprises:
[0067] (1) dispersing a solution containing a thermosetting resin prepolymer and a curing agent into a three-dimensional porous polymer matrix, and pre-curing under a first vacuum condition;
[0068] (2) dispersing a solution containing a thermosetting resin prepolymer and a curing agent into the product obtained in step (1), and curing the product under a second vacuum condition;
[0069] The first vacuum condition and the second vacuum condition each include: a pressure of 0-10 kPa;
[0070] Pre-curing conditions include: temperature of 80-120°C;
[0071] Curing conditions include: temperature of 140-180°C.
[0072] In the present invention, the thermosetting resin prepolymer is pre-cured to make the overall temperature of the sponge uniform, the thermosetting resin inside reaches a gel state, and is attached to the three-dimensional porous polymer matrix skeleton. The vacuum condition is conducive to the gas discharge in the thermosetting resin in the gel state, and better combined with the sponge skeleton. Then, the solution containing the thermosetting resin prepolymer and the curing agent is dispersed on the three-dimensional porous polymer matrix containing the gel-state thermosetting resin, and cured to obtain the oil-absorbing sponge, which is conducive to the uniform distribution of the thermosetting resin on the sponge skeleton, thereby maintaining the elasticity of the three-dimensional porous polymer matrix, improving the recyclable performance of the oil-absorbing sponge, and the adsorption capacity is basically not attenuated when it is recycled for 30 times.
[0073] According to a preferred embodiment of the present invention, in step (1), the gel-state thermosetting resin accounts for 0.5-1% of the total mass of the sponge, which is beneficial to further maintain the elasticity of the three-dimensional porous polymer matrix and improve the recycling performance of the oil-absorbing sponge.
[0074] In the present invention, in step (1), there is no special requirement for the pre-curing time, which can be reasonably adjusted according to actual needs, as long as the thermosetting resin prepolymer forms a gel-state thermosetting resin in the three-dimensional porous polymer matrix. According to a preferred embodiment of the present invention, the pre-curing time is 40-90 minutes.
[0075] In the present invention, in step (2), the curing time is 20-100 minutes.
[0076] According to a preferred embodiment of the present invention, in the solution containing the thermosetting resin prepolymer and the curing agent, the mass concentration of the thermosetting resin prepolymer is 0.02 to 0.6 g / mL, preferably 0.03 to 0.5 g / mL, and more preferably 0.05 to 0.3 g / mL.
[0077] According to a preferred embodiment of the present invention, in the solution containing the thermosetting resin prepolymer and the curing agent, the mass of the curing agent accounts for 1 to 10% of the mass of the thermosetting resin prepolymer; preferably 5 to 10%.
[0078] In the present invention, in the solution containing thermosetting resin prepolymer and curing agent, the optional range of solvent is relatively wide, as long as it can dissolve the thermosetting resin prepolymer and the curing agent. According to a preferred embodiment of the present invention, in the solution containing thermosetting resin prepolymer and curing agent, the solvent is selected from at least one of water, C1-C4 alcohol and C1-C4 ketone; preferably ethanol and / or acetone.
[0079] In the present invention, in the solution containing the thermosetting resin prepolymer and the curing agent, the curing agent has a wide range of options, as long as it can form the thermosetting resin with the thermosetting resin prepolymer. According to a preferred embodiment of the present invention, the curing agent is selected from at least one of organic acids, acid anhydrides, boron trifluoride, aliphatic polyamines and aromatic polyamines; preferably at least one of benzenesulfonic acid, hexamethylenetetramine and meta-phenylenediamine.
[0080] A second aspect of the present invention provides an amine liquid oil removal and recovery method, the method comprising:
[0081] (1) The oil-containing amine liquid inlet 8 and the de-oiled amine liquid outlet 4 are opened, and the dirty oil outlet 5 is closed. The oil-containing amine liquid enters the buffer chamber from the oil-containing amine liquid inlet 8; it flows into the adsorption and filtration chamber from the opening of the partition plate 3, and the oil phase in the oil-containing amine liquid is adsorbed by the adsorption material 6 in the adsorption and filtration chamber to obtain the de-oiled amine liquid; the de-oiled amine liquid flows out from the opening of the pressing plate 9, enters the storage chamber, and is discharged from the de-oiled amine liquid outlet 4;
[0082] (2) When the adsorbent material 6 is saturated with adsorption, the oil-containing amine liquid inlet 8 and the de-oiled amine liquid outlet 4 are closed, the dirty oil outlet 5 is opened, and the connecting rod mechanism 1 is driven to descend, so that the pressing plate 9 squeezes the adsorbent material 6 to discharge the oil phase in the adsorbent material 6. The oil phase flows into the buffer chamber through the opening of the partition plate 3 and is discharged from the dirty oil outlet 5;
[0083] (3) After the oil phase is removed, the connecting rod mechanism 1 is driven to rise, so that the adsorbent material 6 regains its adsorption capacity, and step (1) is repeated. The present invention uses the pressing plate in the amine liquid oil removal and recovery device to squeeze and desorb the oil phase adsorbed by the adsorbent material, and combined with the high resilience of the adsorbent material, the adsorbent material and the oil phase can be separated, thereby realizing the reuse of the adsorbent material; and the amine liquid recovery rate is high, and the oil removal efficiency is greater than 90%.
[0084] In the present invention, there is no particular limitation on the method of driving the link mechanism 1 to rise and fall, as long as the link mechanism 1 can be controlled to rise and fall, for example, it can be driven manually, pneumatically or electrically hydraulically, preferably electrically hydraulically.
[0085] According to a preferred embodiment of the present invention, the maximum load for driving the connecting rod mechanism 1 is greater than 20 kN to ensure that there is enough force to fully squeeze the adsorption material and desorb the oil phase.
[0086] In the present invention, there is no particular limitation on the processing capacity of the oil-containing amine liquid. According to a preferred embodiment of the present invention, the processing capacity of the oil-containing amine liquid is 3 to 5 t / h.
[0087] The present invention will be described in detail below through examples.
[0088] In the following embodiments, the schematic diagram of the amine liquid oil removal and recovery device is as follows: Figure 1 As shown, the amine liquid oil removal and recovery device comprises:
[0089] A first housing 7 and a first accommodating cavity formed by the housing;
[0090] The partition 3 is sealed and arranged in the first accommodating cavity, the bottom of the partition 3 and the first shell 7 form a buffer cavity; the top of the partition 3 and the first shell 7 form a storage cavity;
[0091] A second shell 2 is disposed above the partition 3, and the partition 3 and the second shell 2 form an adsorption filtration chamber; the second shell 2 is welded to the area above the opening of the partition 3;
[0092] The adsorption material 6 disposed in the adsorption filtration chamber is used to adsorb the oil phase in the amine liquid; the adsorption material 6 has super hydrophobic and super oleophilic properties;
[0093] A pressing plate 9 is arranged in the adsorption filter chamber and placed above the adsorption material 6, and the pressing plate 9 squeezes the adsorption material 6 by lifting and lowering;
[0094] The connecting rod mechanism 1 is connected to the pressing plate 9 and penetrates the first shell 7 and the second shell 2, and is used to drive the pressing plate 9 to rise and fall; the partition plate 3 and the pressing plate 9 are provided with openings to provide a flow channel for the fluid, so that the fluid can enter the adsorption and filtration chamber from the buffer chamber through the partition plate 3, and then enter the storage chamber through the pressing plate 9;
[0095] The first housing 7 is provided with an oil-free amine liquid outlet 4, a dirty oil outlet 5 and an oil-containing amine liquid inlet 8 connected to the first accommodating chamber; the oil-free amine liquid outlet 4 is arranged above the partition 3, and the dirty oil outlet 5 and the oil-containing amine liquid inlet 8 are arranged below the partition 3;
[0096] The aperture of the partition 3 is 10 mm, and the material of the partition 3 is 304 stainless steel;
[0097] The opening diameter of the pressing plate 9 is 10 mm;
[0098] In the following examples, the vertical burning test grade is tested according to the UL94 flame retardant test method.
[0099] In the following examples, the saturated oil phase adsorption and the saturated oil phase adsorption after 30 cycles are tested using the following steps: weigh the mass of the sponge to be tested m1, place it in a beaker filled with 200 mL of toluene, weigh the mass of the sponge after adsorption saturation m2, and the saturated oil phase adsorption (Ф): Ф = m1 / m2. The test of the saturated oil phase adsorption after 30 cycles is first to saturate the sponge with toluene, mechanically squeeze it until no oil phase drips naturally, and repeat 30 times. The subsequent test steps are consistent with the saturated oil phase adsorption.
[0100] In the following embodiments, the water contact angle parameters were measured using the EASY DROP contact angle tester from KRUSS, Germany, with a measurement range of 1-180° and a resolution of ±0.1°. A static contact angle measurement mode was used, and a water droplet or white oil droplet with a fixed volume of 2 μL was dropped on the sponge each time. The calculated initial contact angle was taken as the contact angle measurement value of the sponge surface. Six parallel measurements were performed to calculate the average value.
[0101] In the following examples, the oil phase removal rate and oil phase selective adsorption rate of oily wastewater are measured by the following steps: 1000 mL of the same batch of oily wastewater (oil content 10%, oil phase components C7-C9), 10 g of the sample to be tested is weighed, and placed in the above oily wastewater for adsorption for 10 minutes. The volume V1 and oil phase content C1 of the remaining oily wastewater are tested. Oil phase removal rate (β): β = (1-C1V1 / 100) × 100%; oil phase selective adsorption rate (θ): θ = (100-C1V1) / (1000-V1).
[0102] In the following embodiments, the oil removal efficiency test adopts the following steps: the oil phase content of the oil-containing amine liquid before and after passing through the amine liquid oil removal recovery device is tested at the same flow rate and the same temperature. The oil phase content before passing through is C1, and the oil phase content after passing through is C2. The oil removal efficiency (η): η = (1-C2 / C1) × 100%.
[0103] In the following examples, the foaming height and defoaming time of the amine solution were tested with reference to the industry standard SY / T6538-2016 "Formulated Selective Desulfurization Solvents". The foaming height and defoaming time of the amine solution were measured using a foaming tube experiment: nitrogen with a gas velocity of 300 mL / min was used as the disturbance gas, and the experimental temperature was 40°C. Nitrogen was introduced into the foaming tube, and the foaming height H was recorded after the foam height in the tube was stable. The timing was started when the nitrogen was stopped, and the timing was stopped when the foam dissipated and exposed to the water surface, and the defoaming time T was obtained. The higher the foaming height, the longer the defoaming time, and the better the foam stability.
[0104] In the following examples, the porous melamine-formaldehyde sponge matrix (Xuxian Industrial) had a porosity of 95% and an average pore size of 100 μm;
[0105] The porous melamine-formaldehyde sponge matrix (Beiyou Building Materials) has a porosity of 96% and an average pore size of 250 μm.
[0106] Preparation Example 1
[0107] (1) Weigh 10 g of phenolic resin prepolymer solution (plasticized by Meisheng Chemical) and 1 g of hexamethylenetetramine and dissolve them in 200 mL of ethanol. Stir thoroughly to make the solution clear and transparent.
[0108] (2) A 200*200*150 mm porous melamine-formaldehyde sponge matrix (Xuxian Industrial) was measured and the above solution was dispersed into the sponge by extrusion dispersion so that the curing agent solution evenly infiltrated the sponge. The extruded sponge was placed in a vacuum oven at 180°C and 3 kPa for curing for 20 min to obtain an oil-absorbing sponge S1.
[0109] In the oil-absorbing sponge S1, the mass of phenolic resin accounts for 2% of the total mass of the oil-absorbing sponge; the average pore size of the oil-absorbing sponge S1 is 100 μm, the porosity is 95%, the open porosity is 98%, the vertical combustion grade is V-0, the contact angle to white oil is 0°, and the contact angle to water is 152.3°; the saturated oil phase adsorption amount is 40 g / g; the saturated oil phase adsorption amount after 30 cycles is 38 g / g.
[0110] The sponge was tested for saturated oil phase adsorption, oil phase removal rate and oil phase selective adsorption rate after 30 cycles according to the test requirements. The results are shown in Table 1.
[0111] Among them, the SEM image of the oil absorbing sponge S1 is as follows Figure 2 As shown, compared with the melamine-formaldehyde sponge matrix (SEM image as Figure 4 ), the porous skeleton size of the oil-absorbing sponge is slightly larger than that before modification, indicating that the phenolic resin is uniformly solidified on the surface of the porous melamine-formaldehyde sponge matrix skeleton and has through holes, which makes the oil-absorbing sponge highly selective for oil products in oily wastewater and has a large adsorption capacity for oil products.
[0112] Figure 3 The SEM image of the oil-absorbing sponge S1 after 30 cycles. Figure 2 Compared with the above, there is basically no change, so the adsorption capacity of the oil-absorbing sponge has basically not declined when it is recycled 30 times.
[0113] Preparation Example 2
[0114] (1) Weigh 10 g of phenolic resin prepolymer solution (plasticized by Meisheng Chemical), 0.3 g of hexamethylenetetramine and 0.2 g of m-xylylenediamine and dissolve them in 200 mL of ethanol. Stir thoroughly to make the solution clear and transparent.
[0115] (2) Weigh a 200*200*150 mm porous melamine-formaldehyde sponge matrix (Xuxian Industrial), and disperse the above solution into the sponge by extrusion dispersion so that the curing agent solution evenly infiltrates the sponge. Place the sponge after extrusion in a 140° C. vacuum oven for curing for 100 min to obtain an oil-absorbing sponge S2.
[0116] In the oil-absorbing sponge S2, the mass of phenolic resin accounts for 3% of the total mass of the sponge; the average pore size of the oil-absorbing sponge S2 is 100 μm, the porosity is 95%, and the open porosity is 98%; the vertical combustion grade is V-1, the contact angle to white oil is 0°, and the contact angle to water is 153.2°; the saturated adsorption capacity is 38 g / g; the saturated oil phase adsorption capacity after 30 cycles is 37 g / g.
[0117] The sponge was tested for saturated oil phase adsorption, oil phase removal rate and oil phase selective adsorption rate after 30 cycles according to the test requirements. The results are shown in Table 1.
[0118] Preparation Example 3
[0119] (1) Weigh 10 g of epoxy resin prepolymer solution (Willigut) and 0.6 g of hexamethylenetetramine and dissolve them in 200 mL of acetone. Stir thoroughly to make the solution clear and transparent.
[0120] (2) Weigh a 200*200*150 mm porous melamine-formaldehyde sponge matrix (Beyou Building Materials), and disperse the above solution into the sponge by spraying so that the curing agent solution evenly infiltrates the sponge. Place the extruded sponge in a vacuum oven at 150°C and 5 kPa for curing for 20 min to obtain an oil-absorbing sponge S3.
[0121] In the oil-absorbing sponge S3, the mass of epoxy resin accounts for 3% of the total mass of the sponge; the average pore size of the oil-absorbing sponge S3 is 250 μm, the porosity is 96%, and the open porosity is 98%; the vertical combustion grade is V-0; the contact angle to white oil is 0°, and the contact angle to water is 151.1°; the saturated adsorption capacity is 40 g / g; the saturated oil phase adsorption capacity after 30 cycles is 35 g / g.
[0122] The sponge was tested for saturated oil phase adsorption, oil phase removal rate and oil phase selective adsorption rate after 30 cycles according to the test requirements. The results are shown in Table 1.
[0123] Preparation Example 4
[0124] The method of Preparation Example 3 was followed, except that the volume of the porous melamine-formaldehyde sponge matrix was 400*400*150 mm; the other conditions were the same as Preparation Example 3, to obtain oil-absorbing sponge S4.
[0125] In the oil-absorbing sponge S4, the mass of epoxy resin accounts for 0.5% of the total mass of the sponge; the average pore size of the oil-absorbing sponge S4 is 250 μm, the porosity is 92%, and the open porosity is 93%; the vertical combustion grade is V-0; the contact angle to white oil is 0°, and the contact angle to water is 146°; the saturated adsorption capacity is 37 g / g; the saturated oil phase adsorption capacity after 30 cycles is 33 g / g.
[0126] The sponge was tested for saturated oil phase adsorption, oil phase removal rate and oil phase selective adsorption rate after 30 cycles according to the test requirements. The results are shown in Table 1.
[0127] Preparation Example 5
[0128] The method of Preparation Example 3 was followed, except that 20 g of epoxy resin prepolymer solution (Willigut) and 1.2 g of hexamethylenetetramine were weighed and dissolved in 200 mL of acetone; the other conditions were the same as those of Preparation Example 3 to obtain oil-absorbing sponge S5.
[0129] In the oil-absorbing sponge S5, the mass of epoxy resin accounts for 5% of the total mass of the sponge; the average pore size of the oil-absorbing sponge S5 is 240 μm, the porosity is 87%, and the open porosity is 83%; the vertical combustion grade is V-1; the contact angle to white oil is 0°, and the contact angle to water is 155.4°; the saturated adsorption capacity is 32 g / g; the saturated oil phase adsorption capacity after 30 cycles is 30 g / g.
[0130] The sponge was tested for saturated oil phase adsorption, oil phase removal rate and oil phase selective adsorption rate after 30 cycles according to the test requirements. The results are shown in Table 1.
[0131] Preparation Example 6
[0132] (1) Weigh 10 g of phenolic resin prepolymer solution (plasticized by Meisheng Chemical) and 1 g of hexamethylenetetramine and dissolve them in 200 mL of ethanol. Stir thoroughly to make the solution clear and transparent.
[0133] (2) taking a 200*200*150 mm porous melamine-formaldehyde sponge matrix (Xuxian Industrial), dispersing the above solution into the sponge by extrusion dispersion, so that the curing agent solution evenly infiltrates the sponge, and curing the sponge after extrusion in a vacuum oven at 110° C. and 3 kPa for 80 min to obtain a sponge containing a gel-state phenolic resin; wherein the gel-state phenolic resin sponge accounts for 1% of the total mass of the porous melamine-formaldehyde sponge matrix;
[0134] (3) The solution of step (1) is dispersed into the sponge containing the gel-like phenolic resin obtained in step (2) by extrusion dispersion, so that the solution evenly infiltrates the sponge. The extruded sponge is placed in a vacuum oven at 180° C. and 3 kPa for curing for 20 min to obtain an oil-absorbing sponge S6.
[0135] The phenolic resin accounts for 2% of the total mass of the oil-absorbing sponge S6; the average pore size of the oil-absorbing sponge is 100 μm, the porosity is 95%, the open porosity is 98%, the vertical combustion grade is V-0, the contact angle to white oil is 0°, and the contact angle to water is 153.8°; the saturated oil phase adsorption amount is 44 g / g; the saturated oil phase adsorption amount after 30 cycles is 43 g / g.
[0136] Preparation Example 7
[0137] (1) Weigh 10 g of phenolic resin prepolymer solution (plasticized by Meisheng Chemical) and 1 g of hexamethylenetetramine and dissolve them in 200 mL of ethanol. Stir thoroughly to make the solution clear and transparent.
[0138] (2) A 200*200*150 mm porous melamine-formaldehyde sponge matrix (Xuxian Industrial) was measured and the above solution was dispersed into the sponge by extrusion dispersion so that the curing agent solution evenly infiltrated the sponge. The sponge after extrusion was placed in a vacuum oven at 110° C. and 3 kPa for curing for 80 min to obtain a sponge containing gel phenolic resin; the pre-cured sponge was then placed in a vacuum oven at 180° C. and 3 kPa for curing for 20 min to obtain an oil-absorbing sponge S7.
[0139] In the oil-absorbing sponge S7, the mass of phenolic resin accounts for 2% of the total mass of the oil-absorbing sponge; the average pore size of the oil-absorbing sponge S8 is 100 μm, the porosity is 95%, the open porosity is 98%, the vertical combustion grade is V-0, the contact angle to white oil is 0°, and the contact angle to water is 152.7°; the saturated oil phase adsorption amount is 41 g / g; the saturated oil phase adsorption amount after 30 cycles is 40 g / g.
[0140] Preparation Example 8
[0141] The method of Preparation Example 1 was followed, except that the impregnation amount of the phenolic resin prepolymer was adjusted so that the mass of the phenolic resin accounted for 7% of the total mass of the oil-absorbing sponge. The remaining conditions were the same as those of Preparation Example 1, to obtain oil-absorbing sponge D1.
[0142] In the oil-absorbing sponge D1, the mass of phenolic resin accounts for 7% of the total mass of the sponge; the average pore size of the oil-absorbing sponge D1 is 230 μm, the porosity is 73%, and the open porosity is 69%; the vertical combustion grade is V-2; the contact angle to white oil is 0°, and the contact angle to water is 158.1°; the saturated adsorption capacity is 27 g / g; the saturated oil phase adsorption capacity after 30 cycles is 20 g / g.
[0143] Figure 5 is the SEM photo of sponge D1. Compared with oil-absorbing sponge S1 ( Figure 2 ), the skeleton and the joints of the sponge are obviously covered with more phenolic resin, which reduces the porosity of the sponge and the corresponding saturated adsorption capacity. In addition, the phenolic resin is unevenly distributed on the surface of the skeleton, which is prone to stress concentration during the cyclic use process, resulting in skeleton collapse. Figure 6 This is a photo of the skeleton of sponge D1 after being recycled 30 times. The stacking density of the skeleton has increased significantly, resulting in a decrease in the saturated adsorption capacity.
[0144] The sponge was tested for saturated oil phase adsorption, oil phase removal rate and oil phase selective adsorption rate after 30 cycles according to the test requirements. The results are shown in Table 1.
[0145] Preparation Example 9
[0146] The method of Preparation Example 1 is followed, except that in step (2), curing is carried out under normal pressure, specifically: the sponge after extrusion is placed in an oven at 180° C. for curing for 20 minutes, and the other conditions are the same as those of Preparation Example 1, to obtain oil-absorbing sponge D2.
[0147] In the oil-absorbing sponge D2, the mass of phenolic resin accounts for 0.2% of the total mass of the sponge; the average pore size of the oil-absorbing sponge D2 is 250 μm, the porosity is 96%, and the open porosity is 98%; the vertical combustion grade is V-0; the contact angle to white oil is 0°, and the contact angle to water is 133.1°; the saturated adsorption capacity is 30 g / g; the saturated oil phase adsorption capacity after 30 cycles is 20 g / g.
[0148] The sponge was tested for saturated oil phase adsorption, oil phase removal rate and oil phase selective adsorption rate after 30 cycles according to the test requirements. The results are shown in Table 1.
[0149] Examples 1-7 and Comparative Examples 1-2
[0150] The oil-absorbing sponges prepared in Preparation Examples 1-7 and Preparation Examples 8-9 were respectively filled in the adsorption filter chamber, and then the amine solution was recovered. The recovery method was as follows:
[0151] Oil-containing amine liquid filtration working conditions: open the oil-containing amine liquid inlet 8 and the de-oiled amine liquid outlet 4, close the dirty oil outlet 5, the oil-containing amine liquid enters the buffer chamber from the oil-containing amine liquid inlet 8; flows into the adsorption filtration chamber from the opening of the partition plate 3, and the oil phase in the oil-containing amine liquid is adsorbed by the adsorption material 6 in the adsorption filtration chamber to obtain the de-oiled amine liquid; the de-oiled amine liquid flows out from the opening of the pressing plate 9, enters the storage chamber, and is discharged from the de-oiled amine liquid outlet 4;
[0152] Oil discharge working condition: after the sponge is saturated with adsorption, close the oil-containing amine liquid inlet 8 and the de-oiled amine liquid outlet 4, open the dirty oil outlet 5, drive the connecting rod mechanism 1 down, make the pressing plate 9 squeeze the adsorption material 6, discharge the oil phase in the adsorption material 6, and the oil phase flows into the buffer chamber through the opening of the partition plate 3 and is discharged from the dirty oil outlet 5; after the oil phase is discharged, drive the connecting rod mechanism 1 up, make the adsorption material 6 have adsorption capacity again, and then implement the oil-containing amine liquid filtration;
[0153] The processing capacity of the oil-containing amine liquid is 3t / h; the driving connecting rod mechanism 1 has a maximum stroke of 80% of the sponge thickness and a maximum load of 20kN. The treated de-oiled amine liquid is tested for foaming height and defoaming time, and the results are shown in Table 2.
[0154] Comparative Example 3
[0155] According to the method of Example 3, the filled oil-absorbing sponge is an unmodified porous melamine-formaldehyde sponge matrix (Beyou Building Materials) D3, and the other conditions are the same as Example 3.
[0156] Table 2
[0157] serial number Oil absorbing sponge Oil removal efficiency% Foaming height (cm) Defoaming time(s) Example 1 S1 92.6 2.4 2.7 Example 2 S2 93.4 2.5 2.7 Example 3 S3 94.5 2.3 2.6 Example 4 S4 85.3 2.7 3.2 Example 5 S5 91.2 2.5 2.9 Example 6 S6 95.0 2.0 2.4 Example 7 S7 94.8 2.2 2.5 Comparative Example 1 D1 83.2 3.1 3.5 Comparative Example 2 D2 75.6 3.6 4.2 Comparative Example 4 D3 20.7 5.1 5.8
[0158] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. An amine liquid oil removal and recovery device, It is characterized in that The device includes: A first housing (7) and a first accommodating cavity formed by surrounding the first housing (7); A partition (3) is sealed and arranged in the first accommodating cavity, wherein the bottom of the partition (3) and the first shell (7) form a buffer cavity; and the top of the partition (3) and the first shell (7) form a storage cavity; A second shell (2) is arranged above the partition (3), and the partition (3) and the second shell (2) form an adsorption filtration chamber; The adsorption material (6) is arranged in the adsorption filtration cavity and is used to adsorb the oil phase in the amine liquid; the adsorption material (6) has super hydrophobic and super oleophilic properties; A pressure plate (9) is arranged in the adsorption filter chamber and placed above the adsorption material (6), and the pressure plate (9) squeezes the adsorption material (6) by lifting and lowering; the partition plate (3) and the pressure plate (9) are provided with openings to provide a flow channel for the fluid, so that the fluid can enter the adsorption filter chamber from the buffer chamber through the partition plate (3), and then enter the storage chamber through the pressure plate (9); A connecting rod mechanism (1) is connected to the pressing plate (9) and passes through the first shell (7) and the second shell (2), and is used to drive the pressing plate (9) to move up and down; The first shell (7) is provided with an oil-free amine liquid outlet (4), a dirty oil outlet (5) and an oil-containing amine liquid inlet (8) which are connected to the first accommodating chamber; the oil-free amine liquid outlet (4) is arranged above the partition (3), and the dirty oil outlet (5) and the oil-containing amine liquid inlet (8) are arranged below the partition (3).
2. The recovery device according to claim 1, in, The adsorption material (6) comprises an oil-absorbing sponge, which comprises a three-dimensional porous polymer matrix and a thermosetting resin coated on the three-dimensional porous polymer matrix; the saturated adsorption capacity of the oil-absorbing sponge for the oil product is not less than 30 g / g; the saturated adsorption capacity of the oil-absorbing sponge for the oil product is still not less than 30 g / g after 30 cycles of adsorption-desorption.
3. The recovery device according to claim 2, in, The mass of the thermosetting resin accounts for 0.5-5% of the total mass of the sponge; preferably 2-3%; and / or The saturated adsorption capacity of the oil-absorbing sponge for oil products is 30-50 g / g; the saturated adsorption capacity of the oil-absorbing sponge for oil products is still 30-50 g / g after being used in a desorption-adsorption cycle for 30 times.
4. The recovery device according to claim 2 or 3, in, The thermosetting resin is selected from at least one of phenolic resin, epoxy resin, urea-formaldehyde resin, unsaturated polyester resin and silicone resin; preferably selected from at least one of phenolic resin, epoxy resin and silicone resin; and / or The three-dimensional porous polymer matrix is selected from at least one of melamine-formaldehyde sponge, polyurethane sponge and ethylene-vinyl acetate sponge, preferably melamine-formaldehyde sponge.
5. The recovery device according to any one of claims 2 to 4, in, The pore size of the oil absorbing sponge is 10-500 μm; and / or The porosity of the oil-absorbing sponge is greater than or equal to 60%.
6. The recovery device according to any one of claims 2 to 5, in, The static plane contact angle of the surface of the oil-absorbing sponge to water in air is greater than 135°; and / or The static contact angle of the oil-absorbing sponge surface to white oil is less than 30°; and / or The UL94 vertical burning test grade of the oil absorbing sponge is above V-2.
7. The recovery device according to claim 2, in, The preparation method of the oil-absorbing sponge comprises: The solution containing thermosetting resin prepolymer and curing agent is dispersed into a three-dimensional porous polymer matrix, and cured under vacuum conditions to obtain the oil-absorbing sponge; the vacuum conditions include: a pressure of 0-10 kPa.
8. The recovery device according to claim 1, in, The preparation method of the oil absorbing sponge comprises: (1) dispersing a solution containing a thermosetting resin prepolymer and a curing agent into a three-dimensional porous polymer matrix, and pre-curing under a first vacuum condition; (2) dispersing a solution containing a thermosetting resin prepolymer and a curing agent into the product obtained in step (1), and curing the product under a second vacuum condition; The first vacuum condition and the second vacuum condition each include: a pressure of 0-10 kPa; Pre-curing conditions include: temperature of 80-120°C; Curing conditions include: temperature of 140-180°C.
9. The recovery device according to claim 1, in, The material of the partition (3) is selected from one of metal, polymer material or ceramic material; and / or The driving stroke of the connecting rod mechanism (1) is set to 5%-80% of the thickness of the adsorption material (6).
10. A method for recovering oil from amine liquid. It is characterized in that The method includes: (1) The oil-containing amine liquid inlet (8) and the de-oiled amine liquid outlet (4) are opened, and the dirty oil outlet (5) is closed, so that the oil-containing amine liquid enters the buffer chamber from the oil-containing amine liquid inlet (8); flows into the adsorption filtration chamber from the opening of the partition plate (3), and the oil phase in the oil-containing amine liquid is adsorbed by the adsorption material (6) in the adsorption filtration chamber to obtain the de-oiled amine liquid; the de-oiled amine liquid flows out from the opening of the pressing plate (9), enters the storage chamber, and is discharged from the de-oiled amine liquid outlet (4); (2) When the adsorption material (6) is saturated with adsorption, the oil-containing amine liquid inlet (8) and the de-oiled amine liquid outlet (4) are closed, the dirty oil outlet (5) is opened, and the connecting rod mechanism (1) is driven to descend, so that the pressing plate (9) squeezes the adsorption material (6) to discharge the oil phase in the adsorption material (6), and the oil phase flows into the buffer chamber through the opening of the partition plate (3) and is discharged from the dirty oil outlet (5); (3) After the oil phase is removed, the connecting rod mechanism (1) is driven upward so that the adsorption material (6) regains its adsorption capacity and step (1) is repeated.
Citation Information
Patent Citations
Carbon foam biological scaffold as well as preparation method and application thereof
CN101934094A
Oil-water separation device by absorption and extrusion
CN107021540A
Preparation method of flexible epoxy resin oil-water separation sponge
CN108786181A
Superhydrophobic superlipophilic three-dimensional porous material, preparation method therefor and application of superhydrophobic superlipophilic three-dimensional porous material
CN110743200A
Amine liquid purification skid-mounted system and method thereof
CN111056671A
